Acid mine drainage mitigation: A review - Lazo, Daniel (2020)
Acid mine drainage (AMD) or acid rock drainage (ARD) refers to the effluents from coal and metal mines. AMD is a common phenomenon which occurs naturally as a process of rock weathering, but is increased in large scale due to human activities such as construction contracts (transportation corridors, dam build, etc.) and mining operations. This phenomenon denotes the acidic water that is produced during exposure of sulphide minerals (mainly pyrite) to air and water through a natural process, and creates sulphuric acid. AMD is a hazard to animals, aquatic life and human beings as it increases the acidity and dissolves metals. Preventing and treating AMD is an important issue in a mine site not only during operation life but also after the mine is abandoned.